2020
DOI: 10.1007/s11882-020-00969-7
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Patient and Provider Satisfaction with Telemedicine

Abstract: Purpose of Review The purpose of this review is to describe the determinants of satisfaction with telemedicine (TM) and how they compare with in-person visits from both the perspective of patients and of providers. Recent Findings The use of TM will expand only if patients and providers are at least as satisfied with it as they are with in-person visits. Since deviations from expected care can result in reduced satisfaction regardless of the quality of the visit or obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
164
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(184 citation statements)
references
References 36 publications
15
164
1
4
Order By: Relevance
“…The results of this project indicate that Veterans were satisfied with the telerehabilitation wheelchair seating and mobility assessments, consistent with previous research revealing high participant satisfaction with telehealth services ( Donelan et al, 2019 ; Graham et al, 2020 ; Gustke et al, 2000 ; Mair & Witten, 2000 ; Nguyen et al, 2020 ; Ramaswamy et al, 2020 ; Schein et al, 2010b ; Whitten & Love, 2005 ; Williams et al, 2001 ). A previous study by Gustke et al (2000) revealed that patient satisfaction is rated high because the use of telehealth directly removes several problems associated with dissatisfaction in healthcare, such as appointment scheduling and travel time.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The results of this project indicate that Veterans were satisfied with the telerehabilitation wheelchair seating and mobility assessments, consistent with previous research revealing high participant satisfaction with telehealth services ( Donelan et al, 2019 ; Graham et al, 2020 ; Gustke et al, 2000 ; Mair & Witten, 2000 ; Nguyen et al, 2020 ; Ramaswamy et al, 2020 ; Schein et al, 2010b ; Whitten & Love, 2005 ; Williams et al, 2001 ). A previous study by Gustke et al (2000) revealed that patient satisfaction is rated high because the use of telehealth directly removes several problems associated with dissatisfaction in healthcare, such as appointment scheduling and travel time.…”
Section: Discussionsupporting
confidence: 87%
“…This project specifically evaluated the satisfaction of both Veterans and providers during telehealth wheelchair seating and mobility evaluations. Previous research in the field of telehealth show consistent high levels of patient satisfaction, whereas the few studies that have evaluated provider satisfaction demonstrate satisfaction given certain criteria ( Graham et al, 2020 ; Nguyen et al, 2020 ). This project hypothesized that similarly high levels of patient satisfaction would be measured; however, it was predicted that there would be differences in Veteran and provider satisfaction scores.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Existing evidence suggests that leadership engagement, resource availability, clinician design involvement, and workforce development are critical drivers of implementation. [44][45][46] Health systems and policymakers should leverage lessons learned during the COVID-19 pandemic to inform the sustainable adoption of telemedicine. The effective, efficient, and equitable implementation of telemedicine in the ''new normal'' will require attention to clinical and organizational implementation factors alongside structural disparities that may affect patients' access to care.…”
Section: Discussionmentioning
confidence: 99%
“…To encourage the use of telemedicine on a wider scale, the clinical outcomes, cost, availability, and user satisfaction need to be taken into account. 51 Here we list down some recommendations for improvement in patient satisfaction.…”
Section: Policy Implicationsmentioning
confidence: 99%